LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA YANG BERIMPIKASI PADA KINERJA KARYAWAN PT. PABRIK GENTENG MASSOKA KARAWANG - Wahyu Murti; Agus Sudradjat; Triadi (Jurnal Manajemen FE-UB, 2022)
Abstract This study aims to determine the extent of the influence of the work environment, providing compensation to employee performance through job satisfaction at PT. Masokka Tile Factory, Karawang.The data used in this study are primary data collected from respondents' answers based on the questionnaire given, as many as 85 people. The data processing method uses the Path Analysis method with the help of SPSS version 22.0. Statistical testing using individual parameter significance test (t test) and simultaneous significance test (F test).The results showed that simultaneously the work environment variables, compensation and job satisfaction had a significant effect on employee performance. in analysis 3: job satisfaction variable has a significant effect on employee performance.   Keywords: work environment, compensation, job satisfaction and employee performance